The Effectiveness Of Ball Grip Therapy In Stroke Patients: Literature Review - Leya Indah Permatasari; Tania Tiara; Khoirun Ni’am; Delya Aulina (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
The damage resulting from a stroke is due to the blood vessels of the brain getting afflicted. Stroke ranks second in terms of disability and death globally, only preceded by cardiovascular diseases. In 87% of the countries affected by stroke, Indonesia included, it is estimated that stroke is the leading cause for death and disability. This study aims to analyze whether ball grip therapy is effective in stroke patients. This study is descriptive and analytical in nature focusing on the benefits that stroke patients can gain from ball grip therapy. This study used a quantitative approach which stemmed from research based on an electronic literature review. A wealth of research supports that consistent and repetitive use of a rubber ball grip improves muscle strength effectively. This also proves that the treatment in fact has the potential to improve muscle strength as well as speed up blood circulation. Rubber ball grip exercise therapy is recommended as a nursing intervention for managing muscle strength with non-hemorrhagic stroke clients.